"Together we rise": Collaboration and contestation as narrative drivers of the Women's March. (April 2019) - Just, Sine Nørholm; Louise Muhr, Sara
The Women's March is arguably the most important counter-narrative to Trump's post-truth regime, but does it also present a leadership alternative to his populist and authoritarian style? And is this alternative necessarily better than currently dominant social formations? In this paper, we argue that the Women's March is partially configured by similar forces of affective circulation as those governing pro-Trump narratives, but that it is different and better in one important respect. The narratives of the Women's March are driven by both collaboration and contestation, meaning its circulation is both centripetal and centrifugal. We substantiate this claim through a close reading of the narration of the Women's March – from its inception until its first anniversary. Here, we focus particularly on the development from a moment of resistance to a political movement, arguing that this process offers a prototype for conceptualizing a new form of "rebel" or social movement leadership. Hence, the Women's March not only offers a different and better alternative to the leadership of Trump but also an opportunity for promoting and refining leadership theory in the post-heroic vein.